ANALISIS PENGARUH MANFAAT-MANFAAT RELASIONAL TERHADAP KUALITAS RELASIONAL DAN KONSEKUENSINYA PADA KOMUNIKASI WORD OF MOUTH POSITIVE (Positive WOM) DAN LOYALITAS (STUDI EMPIRIS PADA NASABAH PINJAMAN DI BPR âASâ SEMARANG) - Rizal R, Alimuddin; Tjahjaningsih, endang; H Prayitno, Teguh; Marlien, RA. (Proceeding Fakultas Ekonomi, 2014)
This study aimed to examine the influence of Social benefits, Special Services benefits, Trust benefits in customer satisfaction, customer satisfaction to the next customer commitment, and how it impacts the customers commitment to positive WoM communication and Customer Loyalty. This study focused on the customers credit in the Great Prosperous Rural Semarang, which has been a customer for over a year. Purposive sampling technique was taken on the grounds that: the respondents had sufficient experience with a relationship bank, so it can answer the questions posed. The number of respondents that can be processed in this study amounted to 121 people. Processing the data using SPSS for Windows Ver.16. The results showed that there are two hypotheses are rejected, the hypothesis of the impact of the benefits of dedicated service to the customer satisfaction (h2) and the impact of positive WOM communication to Loyalty (H7). As for hypothesis: Social Benefits, and Trust in customer satisfaction (h1, h3) proved significant; Effect of Customer Satisfaction on Customer Commitment (h4) also proved significant, and commitment to positive WOM communication (h5) and Loyalty (h6) also proved significant. Each of influence between these variables showed a positive direction. So the results of this study prove that loyalty and positive WoM communication can be built from the Customer Commitment, and Customer Commitment can be achieved if customers are satisfied and is essentially a relational benefits, namely: social benefits and trust benefits perceived by customers.Keywords: Relational Benefits, Satisfaction, Commitment, Communication WOM, and Customer Loyalty.